Il mito poetico delle rovine di Roma. Note su alcune versioni francesi: Note su alcune versioni francesi (ENTHYMEMA, 2020)
The aim of this article is to present the poetic motif of the ruins of Rome through some little known texts. The large number of adaptations, translations and imitations of this motif make it difficult to establish an order between all of them, their sources and their origins. The sonnet Superbi colli, e voi sacre ruine (1513-21) by Baldassarre Castiglione, the Latin poem De Roma (1554) by Giovanni Vitale (Janus Vitalis) from Palermo and, above all, sonnet III from the book Les Antiquités de Rome (1558) by Joachim Du Bellay have generated numerous imitations and translations until today. The topos of the ruins of Rome is transformed into a myth.Although the most famous poems have been well studied, for example, the famous sonnet A Roma sepultada en sus ruinas (1648) by Quevedo, we want to offer an overview of the spread of the myth and their main variations and oppositions through some less studied French translations and versions.
Keywords: Ruins of Rome; Paul Scarron; Jérôme Hennequin; Jacques Grévin; Poetic translation